Assessment of activization of thought patterns of football players in a coordinated action that ended in scoring a goal - Duda, H.; Rydzik, L.; Czarny, W.; Ras, I.; Ozimek, M.; Ambrozy, T. (Acta Kinesiologica, 2021)
Teaching football should not be focused exclusively on students` physical or locomotor skills, it should also develop their thinking processes. This fact comes as a result of cooperation of football players during a match, which requires anticipation and making right decisions. The process of intellectual training is often outlined by coaches, but in a regular training it is often not discussed in detail, since not many studies confirmed its importance. In the paper the level of thinking of players during cooperation in scoring a goal was discussed as well as modeling of the game using means of intellectual training. The observation of player cooperation included the analysis of 141 goals scored in 76 randomly selected football matches in UEFA Champions League from 2005 to 2019. In the study the method of noted observation was used, the subject of the study could be observed many times. The actions were observed due to the level of thinking processes. The analysis of the results shows that cooperation of the players in order to achieve the ultimate offensive objective of the game requires intentional actions based on thought patterns. These patterns taught in the training can guarantee not only anticipating in the realization of common tasks, but also making decisions that are best for the effectiveness of the game